The Effect of Yoga Practice on Anxiety Levels and Sleep Quality Women of Childbearing Age When Facing Premenstrual Syndrome - Dwi Nandia, Jumiati Riskiyani; Lutfatul Fitriana; Fajar Alam Sukma (Jurnal EduHealth, 2022)
In general, efforts to treat premenstrual syndrome only focus on decreasing the intensity of the menstrual pain scale (dysmenorrhea) through the administration of drugs such as painkillers. However, the use of these drugs does not include the treatment of psychological symptoms experienced by women in the premenstrual syndrome phase. Alternative treatment efforts as non-pharmacological preventive measures are needed to improve the health status of women when they are in the menstrual phase, one of which is by doing yoga exercises. The purpose of this study was to determine the level of anxiety and sleep quality of women of childbearing age during premenstrual syndrome with yoga practice. This study uses a quantitative research method with a pre-experimental approach with one group pre-test and post-test without control design. Sampling technique using Accidental Sampling. The number of research samples was 38 women of childbearing age. Data were collected using an anxiety level questionnaire using a standardized questionnaire (HRS-A) and a sleep quality questionnaire using a standard PSQI questionnaire. Bivariate analysis using Wilcoxon test. The results of the Wilcoxon test statistic obtained a significance value of 0.000, meaning the significance value <α (0.05), meaning that there was a significant change between anxiety before and after the intervention was given. The results of the statistical test of sleep quality obtained a significance value of 0.000, meaning the significance value < (0.05) which means that there is a significant change between sleep quality before and after being given yoga practice interventions in women of childbearing age when facing premenstrual syndrome. The conclusion of this study is that regular yoga practice can reduce anxiety and improve sleep quality for women of childbearing age. Yoga practice can be used as an appropriate non-pharmacological treatment in the treatment of premenstrual syndrome.